Synthesis of SnO2 nanowires forCO, CH4 and CH3OH gases sensing. (August 2018) - Shehzad, Khurram; Shah, Nazar Abbas; Amin, Muhammad; Abbas, Murrawat; Syed, Waqar Adil
Synthesis of one-dimensional nanostructures, such as nanowires, is of vigorous significance for achieving the desired properties and fabricating functional devices. In this work, we report the synthesis of tin oxide (SnO2 ) nanowires on gold-catalyzed silicon substrate by carbothermal reduction process. SnO2 nanowires were synthesized with SnO2 and graphite powders as the source materials at atmospheric pressure and temperature of 900°C in the ambience of nitrogen (N2 ) gas. First, the effect of source material ratio SnO2 :C on growth of SnO2 nanowires was studied. The structural, morphological and compositional properties of the samples were investigated by X-ray diffraction, scanning electron microscopy and energy dispersive X-ray spectroscopy. The scanning electron microscopy investigation reveals that uniform dense nanowires of SnO2 (diameter 127 nm and length 40 µm) were synthesized with vapour–liquid–solid mechanism. Ultraviolet–visible spectra estimate that the optical band gap of the synthesized SnO2 nanowires was 3.72 eV. Second, the gas sensing performance of synthesized SnO2 nanowires was investigated by testing with carbon monoxide (CO), Methane (CH4 ) and methanol (CH3 OH) gases at different operating temperatures and concentrations. Results indicate that the synthesized SnO2 nanowires are highly promising for gas sensing applications.